2020
DOI: 10.2341/19-027-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Peak Light-emitting-diode Curing Unit Beam Homogenization Tips on Microhardness of Resin Composites

Abstract: SUMMARY This study evaluated the effect of light curing unit (LCU) guide type (regular or homogenizing) on top and bottom microhardness of conventional and bulk-fill resin-based composites (RBCs). A polywave light-emitting-diode (LED) LCU (Bluephase Style, Ivoclar Vivadent AG) was used with two different light guides: a regular tip (RT, 935 mW/cm2 emittance) and a homogenizer tip (HT, 851 mW/cm2 emittance). Two conventional RBCs (Herculite Ultra [HER], Kerr Corp; Tetric EvoCeram [TEC], Ivoclar V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 32 publications
1
34
0
3
Order By: Relevance
“…5,6 To overcome those problems, manufacturers developed bulk-fill materials with flowable or highviscosity consistencies. 7 These materials present reduced polymerization shrinkage stress compared to conventional RBCs, 3,5,8,9 and increased depths of cure [10][11][12][13] and are indicated for use in a single increment of 4 mm thick or more, without diminishing their physical properties or the quality of restored teeth. 14 Clinically, a reduction in operative time has been proposed as a positive factor for selecting bulk-fill products; 10,15 however, for light cured bulk-fill RBCs, studies report insufficient polymerization at high depths, that might compromise the clinical success of the restorations as a result of increased cytotoxicity, 16 susceptibility to marginal defects, [16][17][18] and reduced hardness.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 To overcome those problems, manufacturers developed bulk-fill materials with flowable or highviscosity consistencies. 7 These materials present reduced polymerization shrinkage stress compared to conventional RBCs, 3,5,8,9 and increased depths of cure [10][11][12][13] and are indicated for use in a single increment of 4 mm thick or more, without diminishing their physical properties or the quality of restored teeth. 14 Clinically, a reduction in operative time has been proposed as a positive factor for selecting bulk-fill products; 10,15 however, for light cured bulk-fill RBCs, studies report insufficient polymerization at high depths, that might compromise the clinical success of the restorations as a result of increased cytotoxicity, 16 susceptibility to marginal defects, [16][17][18] and reduced hardness.…”
Section: Introductionmentioning
confidence: 99%
“…To better activate these alternative photoinitiators, some LED curing lights (Figure 2c,d) now include additional LED emitters that produce additional light in the violet range of wavelengths 2,20,21,32,36 . Figure 2 (c,d) illustrates that the number and location of these violet and blue light emission peaks can vary between manufacturers, as does the relative contribution of each wavelength peak to the total radiant power output from the LCU.…”
Section: Emission Spectrummentioning
confidence: 99%
“…However, unless the LCU is carefully designed, the addition of several different wavelength LED emitters in the LCU can negatively affect the total amount of blue light present and the overall uniformity of the emitted light beam. This will then change the spectral irradiance received across the resin surface, which may then produce an uneven polymerisation within the RBC 2,21,32,36,49,50 .…”
Section: Emission Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent randomized clinical trials showed that restorations with paste-like bulk-fill composite resins also presented satisfactory results over time 35,36 . In terms of clinical procedures, caution with the light-curing unit is extremely important, since evidences showed that stable irradiance, homogeneity of light beam and wavelength components may influence the degree of conversion, depth of cure and wear of bulk-fill composite resins depending on the type and brand of each bulk-fill material [37][38][39][40] . Indeed, a disadvantage of restoring posterior teeth with bulk-fill composite resin could be that the susceptibility to variance in the irradiance of the light-curing units was shown to be material dependent 21 .…”
Section: Total 12 12mentioning
confidence: 99%